Revealing the Economic Consequences of Group Cohesion - Simon Gächter; Chris Starmer; Fabio Tufano (Institute of Labor Economics (IZA), 2017)
We introduce the concept of "group cohesion" to capture the economic consequences of ubiquitous social relationships in group production. We measure group cohesion, adapting the "oneness scale" from psychology. A comprehensive program of new experiments reveals the considerable economic impact of cohesion: higher cohesion groups are significantly more likely to achieve Pareto-superior outcomes in classic weak-link coordination games. We show that effects of cohesion are economically large, robust, and portable. We identify social preferences as a primary mechanism explaining the effects of cohesion. Our results provide proof of concept for group cohesion as a productive new tool of economic research.
Keywords: C92; D03; 330; weak-link game; coordination; oneness; group cohesion; social relationships; experiments; real groups